Analysis of fundus shape in highly myopic eyes by using curvature maps constructed from optical coherence tomography. - Masahiro Miyake; Kenji Yamashiro; Yumiko Akagi-Kurashige; Akio Oishi; Akitaka Tsujikawa; Masanori Hangai; Nagahisa Yoshimura (PLoS ONE, 2014)
PURPOSE: To evaluate fundus shape in highly myopic eyes using color maps created through optical coherence tomography (OCT) image analysis. METHODS: We retrospectively evaluated 182 highly myopic eyes from 113 patients. After obtaining 12 lines of 9-mm radial OCT scans with the fovea at the center, the Bruch's membrane line was plotted and its curvature was measured at 1-µm intervals in each image, which was reflected as a color topography map. For the quantitative analysis of the eye shape, mean absolute curvature and variance of curvature were calculated. RESULTS: The color maps allowed staphyloma visualization as a ring of green color at the edge and as that of orange-red color at the bottom. Analyses of mean and variance of curvature revealed that eyes with myopic choroidal neovascularization tended to have relatively flat posterior poles with smooth surfaces, while eyes with chorioretinal atrophy exhibited a steep, curved shape with an undulated surface (P<0.001). Furthermore, eyes with staphylomas and those without clearly differed in terms of mean curvature and the variance of curvature: 98.4% of eyes with staphylomas had mean curvature ≥7.8×10-5 [1/µm] and variance of curvature ≥0.26×10-8 [1/µm]. CONCLUSIONS: We established a novel method to analyze posterior pole shape by using OCT images to construct curvature maps. Our quantitative analysis revealed that fundus shape is associated with myopic complications. These values were also effective in distinguishing eyes with staphylomas from those without. This tool for the quantitative evaluation of eye shape should facilitate future research of myopic complications.